2008
DOI: 10.1111/j.1365-2028.2008.00933.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the occurrence of entomopathogenic nematodes in the Central Rift Valley Region of Kenya

Abstract: A survey for entomopathogenic nematodes in the central Rift valley region of Kenya was conducted at altitudes between 1800 and 3000 m above sea level and from croplands and noncropland habitats. The sampling depth was 0–30 cm. GPS (global positioning system) was used to measure site positions. One hundred and twelve soil samples were collected and entomopathogenic nematodes trapped through Galleria mellonella. Entomopathogenic nematode presence was demonstrated by G. mellonella mortality and viable ones bulked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 13 publications
2
24
0
Order By: Relevance
“…S. yirgalemense was described by Nguyen et al (2004) from Yiglemen in Ethiopia, where it was found to be the dominant species. It was also reported from the Central Rift Valley of Kenya (Mekete et al, 2005;Mwaniki et al, 2008). The nematode belongs to the bicornutum-group of six described species, of which the exsheathed IJ has two hornlike structures in the cephalic region (Nguyen, 2007).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…S. yirgalemense was described by Nguyen et al (2004) from Yiglemen in Ethiopia, where it was found to be the dominant species. It was also reported from the Central Rift Valley of Kenya (Mekete et al, 2005;Mwaniki et al, 2008). The nematode belongs to the bicornutum-group of six described species, of which the exsheathed IJ has two hornlike structures in the cephalic region (Nguyen, 2007).…”
Section: Discussionmentioning
confidence: 80%
“…In Kenya, new strains of Heterorhabditis bacteriophora and Heterorhabditis indica have been isolated. Isolates of S. yirgalemense, S. karii and Steinernema weiseri have also been reported from the Central Rift Valley Region of Kenya (Mwaniki et al, 2008). In Ethiopia, the dominant species detected was S. yirgalemense (6.3%), with only two isolates of H. bacteriophora (0.7%) (Mekete et al, 2005).…”
Section: Introductionmentioning
confidence: 84%
“…Recovery rates in tropical and sub-tropical regions were 3% in central Andean region of Colombia (Lopez-Nunez et al, 2007), 6% in Guadeloupe , 6.9% in Ethiopia (Mekete et al, 2005), 7% in Chile (Edgington et al, 2010), 12% in Costa Rica (Uribe-Lorío et al, 2005), 12.08% in Brazil (Dolinski et al, 2008), 13.2% in the Pampas region of Argentina (Stock, 1995), 20.04% in the South Andamans (Prasad et al, 2001a) and 52% in Kenya (Mwaniki et al, 2008). However, comparisons must be made with caution because different sampling approaches and different baiting insects were used in the reported surveys.…”
Section: Discussionmentioning
confidence: 95%
“…However, comparisons must be made with caution because different sampling approaches and different baiting insects were used in the reported surveys. In most of the cases where EPN recovery rates were the highest, either sampling sites were selected based on insect habitats or outbreaks (Uribe-Lorío et al, 2005;Stock, 1995), another baiting insect than G. mellonella was used (Prasad et al, 2001b), or a combination of two nematode extraction methods was used (Mwaniki et al, 2008). The current survey did not consider insect habitats or outbreaks and used only G. mellonella as bait insect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation